Increased Risk of Osteoporosis in Patients With Peptic Ulcer Disease: A Nationwide Population-Based Study. Issue 16 (April 2016) - Wu, Chieh-Hsin; Tung, Yi-Ching; Chai, Chee-Yin; Lu, Ying-Yi; Su, Yu-Feng; Tsai, Tai-Hsin; Kuo, Keng-Liang; Lin, Chih-Lung
Abstract : Abstract: To investigate osteoporosis risk in patients with peptic ulcer disease (PUD) using a nationwide population-based dataset. This Taiwan National Health Insurance Research Database (NHIRD) analysis included 27, 132 patients aged 18 years and older who had been diagnosed with PUD (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] codes 531–534) during 1996 to 2010. The control group consisted of 27, 132 randomly selected (age- and gender)-matched patients without PUD. The association between PUD and the risk of developing osteoporosis was estimated using a Cox proportional hazard regression model. During the follow-up period, osteoporosis was diagnosed in 2538 (9.35 %) patients in the PUD group and in 2259 (8.33 %) participants in the non-PUD group. After adjusting for covariates, osteoporosis risk was 1.85 times greater in the PUD group compared to the non-PUD group (13.99 vs 5.80 per 1000 person-years, respectively). Osteoporosis developed 1 year after PUD diagnosis. The 1-year follow-up period exhibited the highest significance between the 2 groups (hazard ratio [HR] = 63.44, 95% confidence interval [CI] = 28.19–142.74, P < 0.001). Osteoporosis risk was significantly higher in PUD patients with proton-pump-inhibitors (PPIs) use (HR = 1.17, 95% CI = 1.03–1.34) compared to PUD patients without PPIs use. This study revealed a significant association between PUD and subsequent risk of osteoporosis. Therefore, PUD patients, especially those treated with PPIs, should be evaluated for subsequent risk of osteoporosis to minimize the occurrence of adverse events. Abstract : Supplemental Digital Content is available in the text